2016
DOI: 10.1038/srep38292
|View full text |Cite
|
Sign up to set email alerts
|

Diverse specificity of cellulosome attachment to the bacterial cell surface

Abstract: During the course of evolution, the cellulosome, one of Nature’s most intricate multi-enzyme complexes, has been continuously fine-tuned to efficiently deconstruct recalcitrant carbohydrates. To facilitate the uptake of released sugars, anaerobic bacteria use highly ordered protein-protein interactions to recruit these nanomachines to the cell surface. Dockerin modules located within a non-catalytic macromolecular scaffold, whose primary role is to assemble cellulosomal enzymatic subunits, bind cohesin modules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
(69 reference statements)
1
18
0
Order By: Relevance
“…The genome of C. thermocellum DSM1313 (RefSeq NC017304.1) was screened for cohesin-containing proteins, and annotated by NCBI annotation software. New (as reported in Bras et al [ 45 ]) and old terminologies are shown for the scaffoldins, together with their gene loci in strain DSM 1313 and their equivalents in the ATCC 27405 strain. CBM, carbohydrate-binding module; SLH, surface-layer homology; CSBM, cell-surface binding module.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The genome of C. thermocellum DSM1313 (RefSeq NC017304.1) was screened for cohesin-containing proteins, and annotated by NCBI annotation software. New (as reported in Bras et al [ 45 ]) and old terminologies are shown for the scaffoldins, together with their gene loci in strain DSM 1313 and their equivalents in the ATCC 27405 strain. CBM, carbohydrate-binding module; SLH, surface-layer homology; CSBM, cell-surface binding module.…”
Section: Resultsmentioning
confidence: 60%
“…The primary scaffoldin in C. thermocellum, CipA (Clo1313_0627), herein termed as ScaA (Fig. 2 ) according to Bras et al [ 45 ], serves as a binding platform for the catalytic subunits via type I cohesin–dockerin interactions. In addition, C. thermocellum cellulosomes can be assembled into more complex cellulosomal suprastructures (polycellulosome complexes) via secondary scaffoldins.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the use of specificity residue substitution in only one conserved segment of R. cellulolyticum ’s and H. thermocellum ’s dockerin (Cel5A and Xyn10B, respectively) generates homogeneous crystallizable complexes by favorizing a single binding mode . Despite the fact that the dockerin dual binding mode has been proposed to reduce the steric constraints imposed by assembling a large number of different enzymes into a single cellulosome, single binding mode has also been reported for some specific cases as the dockerin of Cel124A exclusively binding to the type I cohesin displayed by membrane‐bound scaffoldin ScaG (previously named OlpC) in H. thermocellum .…”
Section: Introductionmentioning
confidence: 99%
“…A series of type-I cohesin modules, separated by flexible linker regions, act as the anchor points to enzyme-borne dockerin type I modules. While the high affinity type-I cohesin-dockerin interaction dictates the supramolecular assembly of the cellulosome, the C-terminal type-II dockerin attaches the complex to the cell surface, and the carbohydrate-binding module (CBM) binds to the cellulosic substrate 1, [7][8][9] (Fig 1a). Interestingly, the dockerin type-I modules from different enzymes display similar affinity to the different cohesins of the scaffoldin, potentially binding to any position with equivalent probability 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…The immense size of cellulosomes, the presence of flexible intermodular linkers, and potential unspecific binding of enzymes to any position on the scaffoldin subunit make the task of unveiling its structure and regulation challenging. Although the structure of whole cellulosomes remains unknown, several cellulosomal fragments have been solved [7][8][9][15][16][17][18][19][20][21][22][23][24][25][26] , and useful insights has been provided by small-angle X-ray scattering [27][28][29] , cryo-electron microscopy 30 , molecular dynamics simulations 31,32 and single molecule experiments 33 . It is crucial to get a detailed picture of their structural organization to understand the synergistic effects encountered in cellulosomes, and, as a key element in cellulosome self-assembly, the role of cohesin-dockerin interaction in its fine structure and regulation.…”
Section: Introductionmentioning
confidence: 99%